1996
DOI: 10.1007/bf00020486
|View full text |Cite
|
Sign up to set email alerts
|

New potential markers of in vitro tomato morphogenesis identified by mRNA differential display

Abstract: The identification of plant genes involved in early phases of in vitro morphogenesis can not only contribute to our understanding of the processes underlying growth regulator-controlled determination, but also provide novel markers for evaluating the outcome of in vitro regeneration experiments. To search for such genes and to monitor changes in gene expression accompanying in vitro regeneration, we have adapted the mRNA differential display technique to the comparative analysis of a model system of tomato cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Both alleles may act in combination with other alleles of either tomato or the wild relatives S. peruvianum or S. chilense [22,25]. On the other hand, Torelli et al [26] identified a cDNA by mRNA-differential display that corresponded to the LESK1 gene and whose expression is specifically and transiently enhanced by the exposure to the hormonal treatment leading to caulogenesis (shoot induction). This gene encodes a putative serine-threonine kinase and has been reported as an in vitro caulogenesis marker in tomato [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Both alleles may act in combination with other alleles of either tomato or the wild relatives S. peruvianum or S. chilense [22,25]. On the other hand, Torelli et al [26] identified a cDNA by mRNA-differential display that corresponded to the LESK1 gene and whose expression is specifically and transiently enhanced by the exposure to the hormonal treatment leading to caulogenesis (shoot induction). This gene encodes a putative serine-threonine kinase and has been reported as an in vitro caulogenesis marker in tomato [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported molecular markers were associated with increasing the in vitro shoot formation (Koornneef et al 1993, Torelli et al 1996, Takashina et al 1998. The AFLP markers detected in the present research were associated with a reduction in the regeneration capacity of the RILs.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 47%
“…Koornneef et al (1993) mapped a high regeneration QTL to chromosome III in an interspecific tomato cross by RFLP analysis. Torelli et al (1996) detected by the differential display technique, some specific mRNA transcripts expressed during the earlier incubation period of tomato explants that were associated to the shoot formation capacity, while Takashina et al (1998) found at least two RAPD and one isoenzymatic markers linked to the high regeneration capacity of the wild L. chilense.The objective of this research was to evaluate both the in vitro callus production and shoot formation, and to detect cosegregating AFLP markers in a set of elite tomato genotypes. Our ultimate goal was to contribute to the knowledge of the inheritance of in vitro culture response of the tomato.…”
mentioning
confidence: 98%
“…Searches of EMBL, as well as TIGR Arabidopsis thaliana EST databank revealed no match for most of the clones. Unknown differential displayed clones were also reported in mammals and plants (Benito et al 1996;Blanchard and Cousins 1996;Torelli et al 1996;Abts et al 1997;Mason and Davis 1997). According to the principle of DDRT-PCR the anchor primer should anneal to the poly(A) + tail, and the amplified product will represent the non-coding 3'-end and only in part a region of the coding strand.…”
Section: Resultsmentioning
confidence: 98%